Comparison of Usage of Conventional and Newer Oral Hypoglycemic Drugs in Type 2 Diabetes Mellitus - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Comparison of Usage of Conventional and Newer Oral Hypoglycemic Drugs in Type 2 Diabetes Mellitus